Mobile-Based Flood Response System - Ahmad, Mohamad Ousama Ashour (2010)
Floods cause many problems and damages to the countries which exposed to such disaster. This damage may be in personal or general, and its cost the government a lot of loss in infrastructure and property, which affect on economy and public money. It is very important to have a system which alert us before or during the floods, this system will response and manage all the activities and procedure that will taken by anti-flood organizations and agencies working in this area. This system will decrease economic and human losses by providing a fully and efficient observing of broadcast status and information. The study concludes that a good Warning System that can release warning in advance. It can change the existing scenario substantially and render informed decision making in adopting proper measures towards flood preparedness, mitigation, control, planning and management. This kind of advance warning can help the authorities for better flood preparedness and also well flood mitigation.